Evaluasi Kinerja Keungan Dengan Menggunakan Strategic Variance Analysis - Hasanah, Nurul (Universitas Pendidikan Indonesia, 2020)
AbstractThis study aims to evaluate the financial performance of Satuan Pendidikan Kerjasama X, a privately-owned Education Operation Unit in Jakarta. The growing amount of SPK schools in Jakarta demands a good competitive strategy with regards to cost leadership and product differentiation to better position the school in the market. The problem in this study is the absence of an evaluation method to assess the effectiveness of the implemented strategy and this research attempts to use Strategic Variance Analysis (SVA) to evaluate the change in the school’s operating income between the period of 2017-2018 and 2018-2019 academic year in the context of growth, price recovery, productivity and capacity underutilization components. This research was designed using a single case study with a mixed-method approach. The data used are primary data collected from interviews and document analysis (in the form of the school’s financial data). Data analysis was conducted using descriptive qualitative analysis approach. The study indicates that the growth, price-recovery, productivity and capacity underutilization components are showing unfavourable results. The declining student number, the increase of teachers’ remuneration and fee discount are the main causes of the decrease in operating income, while 77% of operating income drop comes from productivity component. It shows that the focused differentiation strategy implemented has not shown effective results and the school needs to increase its cost efficiency by considering the results shown by SVA in preparing for the upcoming budgeting. Keywords: Competitive Strategy; Financial Performance; Strategic Variance Analysis; Education Operation UnitAbstrakPenelitian ini bertujuan untuk mengevaluasi kinerja Keuangan pada Satuan Pendidikan Kerjasama (SPK) X, sebuah sekolah swasta internasional yang beroperasi di daerah Jakarta. Berkembangnya jumlah sekolah SPK di Jakarta menuntut adanya strategi kompetitif yang bagus dalam hal efisiensi biaya dan diferensiasi produk untuk memposisikan sekolah lebih baik dalam pasar. Masalah dalam studi ini adalah ketiadaan metode penilaian efektivitas strategi yang diimplementasikan dan penelitian ini berusaha untuk menggunakan Strategic Variance Analysis (SVA) untuk mengevaluasi perubahan pada pendapatan usaha sekolah di antara periode tahun ajaran 2017-2018 dan 2018-2019 dalam konteks komponen pertumbuhan, pemulihan harga, produktivitas dan utilisasi kapasitas. Penelitian ini dirancang sebagai studi kasus dengan pendekatan metode campuran. Data yang digunakan adalah data primer yang diperoleh dari wawancara dan analisis data keuangan sekolah. Analisis data dilakukan menggunakan descriptive qualitative analysis. Hasil penelitian menunjukkan komponen pertumbuhan, pemulihan harga, produktivitas dan utilisasi kapasitas tidak memuaskan. Penurunan jumlah siswa, peningkatan gaji guru dan pemberian diskon adalah penyebab utama penurunan pendapatan usaha dan 77% dari perubahan pendapatan usaha berasal dari komponen produktivitas sehingga dapat disimpulkan strategi diferensiasi terfokus yang diterapkan tidak menunjukkan hasil yang efektif dan sekolah perlu meningkatkan efisiensi biaya dengan mempertimbangkan hasil yang diperoleh dari SVA untuk penyusunan anggaran berikutnya.Kata kunci: Strategi Kompetitif; Kinerja Keuangan; Strategic Variance Analysis; Satuan Pendidikan Kerjasama.